The relationship between childhood maltreatment and its effects on self esteem among youth - Razak, Nurul Nabilah Abdul; Perveen, Asma (University of Muhammadiyah Malang, 2024)
This present study aimed to investigate the relationship between childhood maltreatment and its effect on self-esteem among youth. This study was conducted through the survey method, using an online survey via Google Form for the respondents. The total number of respondents received is 156 (n =156) participants from youth aged 18 to 30, with 74 (47.4%) male respondents and 82 (52.6%) female respondents who are willing to participate in the study. Instruments used in this study were the Childhood Trauma Questionnaire (CTQ) and the Rosenberg Self-Esteem Scale (RSES). This research includes the use of descriptive analysis for the demographic information. Meanwhile, the research hypothesis was tested using Pearson’s correlation to obtain the results between the two variables. Results indicated that emotional neglect has the highest number of childhood maltreatment experiences by youth, but emotional abuse has the most severe case. Childhood maltreatment had a strong negative correlation with self-esteem (r(156) = 0.671, p <0.001). Among the respondents, the increase in the level of childhood maltreatment was correlated with a decrease in self-esteem. Through this study, screening children’s conditions and environment early with extensive intervention is essential to preventing such adverse complications.